Kajian Mutu Ikan Lele (Clarias batrachus) Asap Kering - Raida Agustina; Hendri Syah; Muhammad Ridha (Agricultural Faculty, 2013)
Catfish is health food which contains good nutritional values. Aceh people frequently consume this fish in fresh with complicated special recipe, so that the rate consumption of this fish is still low. Therefore, it is important to find the method for preserving this fish to improve its consumption. Liquid smoke can be used as one method to prepare the fish. The purpose of this study is to assess the quality of catfish under the treatments with and without soaking the fish in liquid smoke.Catfish was cleaned and washed, then it was dipped in solution with 2% salt for 30 min. Afterthat, catfish were air-dried for about 1 hour. About 200 ml of liquid smoke was diluted in 9800 ml water. After soaking in solution with 2% liquid smoke for 10min, catfish were dried by using a cabinet dryer which has three layers. The parameters observed were moisture content and sensory analysis. About 25 panelists had evaluated the samples for appearance, flavor, taste, texture, and color.The results showed that the combination process of smoking and drying might maintain the product quality. The moisture contents of all products were still in appropriate amount as required by the Indonesian Standar (SNI). According to organoleptic test, the smoke-dried catfish was preferred by panelist than the unsmoked-dried one. Therefore, soaking catfish in liquid smoke can be used to improve the taste of the fish. Further study is recommended to evaluate the shelf life of smoke-dried catfish.